A PVDF hollow fiber membrane and its preparation method and use

By performing blending reaction and ultraviolet cross-linking treatment in PVDF hollow fiber membranes, a film with a semi-interpenetrating structure is formed, which solves the problems of insufficient hydrophilicity, pollution resistance and mechanical properties of PVDF membranes, and achieves higher water Flux and better pollutant separation effect.

CN114471192BActive Publication Date: 2025-02-07JIANGSU JIUWU HITECH +1

Patent Information

Application Number
CN202111631143.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-28
Publication Date
2025-02-07
Estimated Expiration
2041-12-28

AI Technical Summary

Technical Problem

The existing PVDF hollow fiber membranes have poor hydrophilicity, low anti-pollution and poor mechanical properties, making it difficult to effectively treat proteins and oligosaccharides in soy whey wastewater.

Method used

By blending PVDF, photoinitiator, initiator and hydrophilic monomer, a primary hollow fiber membrane was prepared by dry-wet method, and ultraviolet cross-linking was performed through an ultraviolet irradiation box to form a purple with a semi-interpenetrating structure. Dixially linked PVDF hollow fiber membrane.

Benefits of technology

It improves the hydrophilicity and mechanical properties of the membrane, increases the water flux, improves the anti-pollution property, improves the protein retention rate and the transmittance of oligosaccharides, and extends the service life of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114471192B_ABST
    Figure CN114471192B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of hollow fiber membranes, and to a PVDF hollow fiber membrane and a preparation method and use thereof. In the present invention, a nascent hollow fiber membrane having a hydrophilic photoinitiator molecular chain is subjected to ultraviolet irradiation to cause a cross-linking reaction to form a semi-interpenetrating structure, and a hydroxyl hydrophilic group is generated at the same time, so that the hydrophilicity and mechanical properties of the membrane are improved, the reaction degree is easy to control, and continuous operation can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hollow fiber membrane technology, specifically to an ultraviolet cross-linked PVDF hollow fiber membrane. Background Technology

[0002] In recent years, with industrial and economic development and population growth, the discharge of wastewater and sewage has increased accordingly, putting increasing pressure on the environment and seriously endangering the ecological environment and human health. Membrane water treatment technology, due to its simplicity, efficiency, and environmental friendliness, has gradually become one of the important ways to solve industrial wastewater and urban sewage discharge and achieve efficient recycling. Polyvinylidene fluoride (PVDF), due to its excellent chemical stability, thermal stability, radiation resistance, good mechanical properties, and ease of film formation, has become one of the main membrane materials on the market and is widely used in various water treatment industries. However, its low surface energy and strong hydrophobicity prevent PVDF membranes from achieving high flux. Furthermore, pollutants such as proteins are easily adsorbed onto the membrane surface due to hydrophobic interactions, resulting in poor antifouling performance and further reducing flux. Frequent rinsing can also damage the membrane surface structure and reduce membrane lifespan. In addition, PVDF hollow fiber homogeneous membranes have poor mechanical properties and are prone to flattening, folding, and breakage under harsh conditions, further limiting their application. Therefore, it is necessary to effectively modify PVDF hollow fiber homogeneous membranes to improve their hydrophilicity, mechanical properties and antifouling properties, extend their service life and broaden the application fields of PVDF hollow fiber membranes.

[0003] The main methods for modifying PVDF membranes include physical blending, surface coating, and surface chemical modification. Patent CN110201559A discloses a high-flux reinforced hollow fiber membrane, where blending the hydrophilic agent triethanolamine with PVDF material improves the membrane's hydrophilicity. Patent CN200410024928 discloses a method for preparing a hydrophilic polyvinylidene fluoride microporous membrane, where polyvinyl alcohol, chitosan, or polyacrylic acid are coated onto the membrane surface to improve its hydrophilicity. Patent CN106334463B discloses an antifouling polyvinylidene fluoride hollow fiber membrane, which uses chemical agents such as sodium borohydride to treat the membrane surface, introduce active sites, fix the initiator to the membrane surface using 2-bromoisobutyryl bromide, and graft amino acid methacrylamide or amino acid methacrylate onto the membrane surface using the SI-ATRP method. This membrane exhibits excellent hydrophilicity and antifouling properties. The aforementioned patents have improved the hydrophilicity, mechanical properties, and antifouling performance of hollow fiber membranes to some extent. However, blended modified membranes are difficult to prepare with uniform pore structures due to uneven dispersion, poor compatibility, and small molecules in the blends. Furthermore, small molecules are easily washed away during later use, leading to a sharp decline in membrane performance. In coated membranes, the coating layer and the membrane layer are only interacted by weak van der Waals forces, resulting in poor interfacial bonding and easy peeling, which leads to decreased membrane performance and degradation. Surface chemical modification involves the use of numerous chemicals, is complex, and is detrimental to the environment and human health, with poor controllability of chemical reaction efficiency and extent. Therefore, a simpler, safer, and more effective modification method is needed to improve the overall performance of PVDF hollow fiber membranes.

[0004] In addition, soybean whey wastewater mainly originates from the production process of soy protein isolate using the alkali dissolution and acid precipitation method. This method discharges 30-50 cubic meters of wastewater per ton of soy protein isolate produced. 3 Soybean whey wastewater contains large amounts of whey protein, ash, and oligosaccharides. It is typically treated biochemically before being discharged, leading to resource waste and increased production costs for manufacturers. Furthermore, when attempting to recover the protein using ultrafiltration membranes, the protein cannot be effectively separated from the oligosaccharides, resulting in a low separation coefficient and hindering the reuse process. Summary of the Invention

[0005] The first objective of this invention is to solve the technical problems of poor hydrophilicity, low antifouling properties, and poor mechanical properties of existing PVDF hollow fiber membranes. The technical solution of this invention to solve the aforementioned hollow fiber membrane technical problems is to provide an ultraviolet cross-linked PVDF hollow fiber membrane, characterized by the following steps: PVDF, photoinitiator, initiator and hydrophilic monomer are blended and reacted to prepare a nascent hollow fiber membrane by a dry-wet method, and then the membrane is irradiated by an ultraviolet irradiation chamber to obtain an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0006] The second objective of this invention is to address the problem in the prior art where, when reusing soybean whey wastewater, the protein cannot be effectively retained while oligosaccharides can permeate. In the method of this invention, the in-situ ultraviolet crosslinking of hydrophilic monomers increases the hydrophilicity of the membrane, making it easier for hydrophilic oligosaccharides to permeate. Furthermore, the ultraviolet crosslinking treatment narrows the pore size distribution of the membrane, reducing the macropores on the membrane surface and thus increasing the protein retention rate.

[0007] A PVDF hollow fiber membrane, the main body of which is made of PVDF material, and which also contains repeating unit structures as shown in the following formula:

[0008]

[0009] The above-mentioned method for preparing PVDF hollow fiber membranes includes the following steps:

[0010] Step 1: Mix PVDF, photoinitiator, solvent, additives, initiator, and hydrophilic monomer, and react them to obtain casting solution;

[0011] Step 2: Hollow fiber membrane fibers are prepared by spinning the casting solution and then phase-transformed in the coagulation solution to obtain a hollow fiber membrane.

[0012] Step 3: Expose the hollow fiber membrane to ultraviolet light irradiation.

[0013] In step 1, the mass ratio of PVDF:photoinitiator:solvent:additive:initiator:hydrophilic monomer is 15-25:0.1-1:45-65:5-18:0.1-1:1-10.

[0014] In step 1, the photoinitiator is 4-acryloyloxybenzophenone (4-ABP).

[0015] In step 1, the hydrophilic monomer is one of acrylamide, methyl acrylate, n-butyl acrylate, and butyl methacrylate.

[0016] In step 1, the initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0017] In step 1, the solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, tetrahydrofuran, and glacial acetic acid.

[0018] In step 1, the additive is at least one of polyvinylpyrrolidone-k30, polyvinylpyrrolidone-k90, ethylene glycol, propylene glycol, glycerol, polyethylene glycol, LiCl, CaCl2, and polyvinyl alcohol.

[0019] In step 1, the reaction conditions are: reaction at 40-80℃ for 2-10 hours under inert gas conditions.

[0020] The inert gas is nitrogen or argon.

[0021] In step 2, the conditions during the spinning process are: the casting solution and the core solution are extruded under a pressure of 0.1-0.5 MPa and an extrusion flow rate of 7-20 m / min.

[0022] In step 2, the core fluid temperature is 15-75℃, and the composition is water or a mixture of water and ethanol, glycerol, solvent or Tween-80 and Span-20.

[0023] In step 2, the coagulation bath temperature is 15-75℃, and the composition is water or a mixture of water and solvent.

[0024] In step 2, before coagulation, the membrane fibers pass through an air bath of 1-30cm.

[0025] In step 3, the ultraviolet irradiation power is 250W and the irradiation time is 5-20min.

[0026] The above-mentioned application of PVDF hollow fiber membranes in liquid filtration.

[0027] The liquid filtration mentioned refers to the separation of protein and total sugar from soybean whey wastewater.

[0028] Beneficial effects

[0029] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0030] (1) The present invention prepares PVDF hollow fiber membrane by free radical copolymerization-dry and wet spinning-ultraviolet crosslinking. It has a semi-interpenetrating network structure, which improves the mechanical properties of the membrane. It has high tensile strength and elongation at break, is not prone to filament breakage or filament folding, has a long service life, and can be adapted to applications in harsh environments.

[0031] (2) The reactant monomers in this invention have numerous hydrophilic groups such as hydroxyl groups. After ultraviolet crosslinking, hydroxyl groups are also generated. The membrane has excellent hydrophilicity, the membrane water flux is increased, and a hydration layer is easily formed on the surface to block protein and organic pollution. The membrane antifouling is significantly improved, and the flux recovery rate of the membrane is high after backwashing.

[0032] (3) The present invention can control the membrane pore size by controlling the blend ratio and the ultraviolet light irradiation time. The pore size range can be controlled within 10-30nm, and it has a high retention effect on general organic matter. Attached Figure Description

[0033] Figure 1 This is a scanning electron microscope image of the hollow fiber membrane in one embodiment of the UV crosslinked PVDF hollow fiber membrane and its preparation method according to the present invention.

[0034] Figure 2 The pore size distribution characterization results are shown for the hollow fiber membrane prepared in this invention.

[0035] Figure 3 The flux change curves are shown in the separation of soybean whey wastewater.

[0036] Figure 4 A comparison of the separation effects of protein and total sugar in the treatment of soybean whey wastewater. Detailed Implementation

[0037] This invention provides an ultraviolet-crosslinked PVDF hollow fiber membrane and its preparation method. The invention involves subjecting a nascent hollow fiber membrane with hydrophilic photoinitiator molecular chains to ultraviolet irradiation, causing a crosslinking reaction to form a semi-interpenetrating structure. Simultaneously, hydrophilic hydroxyl groups are generated, improving the membrane's hydrophilicity and mechanical properties. The reaction degree is easily controlled, allowing for continuous operation. This method utilizes the photoinitiator 4-ABP and a hydrophilic monomer in a PVDF solution for free radical polymerization. The synthesized molecular chains are interwoven with the PVDF molecular chains. Nascent PVDF hollow fiber membranes are prepared using a dry-wet spinning technique. Upon ultraviolet irradiation, the photoinitiator undergoes a hydrogen abstraction reaction. Excited photoinitiator molecules abstract hydrogen atoms from low-molecular-weight oligomers, forming active free radicals that initiate the crosslinking reaction. In this way, the PVDF molecular chains are interwoven within a network structure, forming a semi-interpenetrating structure, thus improving the membrane's mechanical properties. Meanwhile, the free radical comonomer has numerous hydroxyl groups, and the cross-linked substances also produce hydroxyl groups, which improves the overall hydrophilicity of the membrane and makes it durable, increases membrane flux, and improves antifouling properties.

[0038] The reaction mechanism of the above process is as follows:

[0039]

[0040] Example 1

[0041] (1) PVDF, 4-ABP, N,N-dimethylformamide, polyvinylpyrrolidone-k30, azobisisobutyronitrile and acrylamide were blended and reacted with nitrogen gas at 70°C in a water bath for 6 hours. After standing to remove bubbles, a casting solution was obtained. The mass ratio of PVDF:4-ABP:N,N-dimethylformamide:polyvinylpyrrolidone-k30:azobisisobutyronitrile:acrylamide was 15:0.2:65:15:0.1:4.7.

[0042] (2) The casting solution in step (1) and 20wt% N,N-dimethylformamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 18m / min. After passing through an air bath height of 5cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a nascent PVDF hollow fiber membrane.

[0043] (3) The nascent PVDF hollow fiber membrane prepared in step (2) is passed through an ultraviolet irradiation chamber for 5 minutes and 250W to prepare an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0044] Example 2

[0045] (1) PVDF, 4-ABP, N,N-dimethylformamide, polyvinylpyrrolidone-k30, azobisisobutyronitrile and methyl acrylate were blended and reacted with nitrogen gas at 70°C in a water bath for 8 hours. After standing to remove bubbles, a casting solution was obtained. The mass ratio of PVDF:4-ABP:N,N-dimethylformamide:polyvinylpyrrolidone-k30:azobisisobutyronitrile:methyl acrylate was 18:0.6:61:15:0.3:5.1.

[0046] (2) The casting solution in step (1) and 20wt% N,N-dimethylformamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 15m / min. After passing through an air bath height of 2cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a nascent PVDF hollow fiber membrane.

[0047] (3) The nascent PVDF hollow fiber membrane prepared in step (2) is passed through an ultraviolet irradiation chamber for 8 minutes and 250W to prepare an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0048] Example 3

[0049] (1) PVDF, 4-ABP, N,N-dimethylacetamide, polyvinylpyrrolidone-k30, glycerol, azobisisobutyronitrile and n-butyl acrylate were blended and reacted with nitrogen gas at 70°C in a water bath for 8 hours. After standing to remove bubbles, a casting solution was obtained. The mass ratio of PVDF:4-ABP:N,N-dimethylacetamide:polyvinylpyrrolidone-k30:glycerol:azobisisobutyronitrile:n-butyl acrylate was 18:0.6:59:12:5:0.3:5.1.

[0050] (2) The casting solution in step (1) and 20wt% N,N-dimethylacetamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 15m / min. After passing through an air bath height of 5cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a nascent PVDF hollow fiber membrane.

[0051] (3) The nascent PVDF hollow fiber membrane prepared in step (2) is passed through an ultraviolet irradiation chamber for 8 minutes and 250W to prepare an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0052] Example 4

[0053] (1) PVDF, 4-ABP, N,N-dimethylacetamide, polyvinylpyrrolidone-k30, polyvinyl alcohol, dimethyl azobisisobutyrate and acrylamide were blended and reacted with nitrogen gas at 70°C in a water bath for 8 hours. After standing to remove bubbles, a casting solution was obtained. The mass ratio of PVDF:4-ABP:N,N-dimethylacetamide:polyvinylpyrrolidone-k30:polyvinyl alcohol:dimethyl azobisisobutyrate:acrylamide was 19:0.4:60:15:1:0.2:4.4.

[0054] (2) The casting solution in step (1) and 20wt% N,N-dimethylacetamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 12m / min. After passing through an air bath height of 10cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a nascent PVDF hollow fiber membrane.

[0055] (3) The nascent PVDF hollow fiber membrane prepared in step (2) is passed through an ultraviolet irradiation chamber for 5 minutes and 250W to prepare an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0056] Example 5

[0057] (1) PVDF, 4-ABP, N,N-dimethylacetamide, polyvinylpyrrolidone-k30, polyethylene glycol-2000, dimethyl azobisisobutyrate and butyl methacrylate were blended and reacted with nitrogen gas at 70°C in a water bath for 8 hours. After standing to remove bubbles, a casting solution was obtained. The mass ratio of PVDF:4-ABP:N,N-dimethylacetamide:polyvinylpyrrolidone-k30:polyethylene glycol-2000:dimethyl azobisisobutyrate:butyl methacrylate was 20:0.4:59:10:6:0.2:4.4.

[0058] (2) The casting solution in step (1) and 20wt% N,N-dimethylacetamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 12m / min. After passing through an air bath height of 2cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a nascent PVDF hollow fiber membrane.

[0059] (3) The nascent PVDF hollow fiber membrane prepared in step (2) is passed through an ultraviolet irradiation chamber for 5 minutes and 250W to prepare an ultraviolet cross-linked PVDF hollow fiber membrane with a semi-interpenetrating structure.

[0060] Comparative Example 1

[0061] The difference from Example 5 is that hydrophilic monomers and UV curing were not used in the preparation process.

[0062] (1) PVDF, N,N-dimethylacetamide, polyvinylpyrrolidone-k30, and polyethylene glycol-2000 are blended and reacted with nitrogen gas at 70°C in a water bath for 8 hours. After standing to remove bubbles, a casting solution is obtained. The mass ratio of PVDF:N,N-dimethylacetamide:polyvinylpyrrolidone-k30:polyethylene glycol-2000 is 20:59:10:6.

[0063] (2) The casting solution in step (1) and 20wt% N,N-dimethylacetamide core solution (25℃) are extruded into a columnar liquid film through an annular spinneret under a pressure of 0.3MPa and a spinning speed of 12m / min. After passing through an air bath height of 2cm, the columnar liquid film enters a 45℃ pure water coagulation bath and is then washed in a water washing tank to obtain a PVDF hollow fiber membrane.

[0064] Test method:

[0065] Pore ​​size and distribution were obtained by dry-wet method testing, using a 70% glycerol-water mixture for pre-soaking, and the parameters were converted into pore size and distribution parameters by gas pressure.

[0066] Mechanical properties were obtained by testing with a tensile testing machine.

[0067] The contact angle is obtained by taking a photograph using a contact angle tester.

[0068] Pure water flux is obtained directly through pressure filtration using a filtration device.

[0069] In the filtration experiment, soybean whey wastewater was used for testing. The wastewater had a COD of approximately 21,500 mg / L, a pH of 4.20-4.45, a protein content of 0.63%, and a total sugar content of 1.24%. The whey protein content was determined using the biuret method, and the total sugar content was analyzed using the anthrone colorimetric method. Before the filtration experiment, pre-filtration was performed using a ceramic microfiltration membrane with an average pore size of 500 nm to remove larger suspended solids. The ultrafiltration membrane separation process was conducted at an operating pressure of 0.4 MPa and a temperature of 25-30℃.

[0070] The pore size distribution diagrams of the ultrafiltration membranes obtained in Example 5 and Comparative Example 1 are shown below. Figure 2 As shown in the figure, after ultraviolet crosslinking treatment, not only is the average pore size of the membrane effectively reduced, but the pore size distribution of the membrane is also made more concentrated, resulting in a narrower distribution rate.

[0071] The physical performance characterization test results of Example 5 and Comparative Example 1 show that the method of this patent, due to the application of hydrophilic monomers, not only improves the water flux of the membrane, but also improves the physical performance of the membrane through ultraviolet crosslinking.

[0072]

[0073]

[0074] During the separation of whey protein wastewater, the change in membrane flux decay rate is as follows: Figure 3 As shown in the figure, the ultrafiltration membrane prepared in Example 5 exhibits significantly less flux decay during separation than that in Comparative Example 1. This is partly due to the increased surface hydrophilicity of the membrane and partly due to the narrower pore size distribution of the membrane, which avoids membrane blockage caused by large pores.

[0075] During the separation process, the test results for protein retention rate and total sugar permeability are as follows: Figure 4 As shown in the figure, the ultrafiltration membrane obtained after UV crosslinking treatment exhibits a higher protein rejection rate and better polysaccharide permeability, resulting in better separation performance. On the one hand, by increasing the hydrophilicity of the membrane, oligosaccharides rich in hydroxyl groups on the surface can more easily permeate; on the other hand, due to the narrower pore distribution after UV crosslinking treatment, the macropores on the membrane surface are reduced, thus increasing the protein rejection rate.

Claims

1. Application of PVDF hollow fiber ultrafiltration membrane in the separation of protein and total sugar in soybean whey wastewater, the ultrafiltration membrane makes oligosaccharides more permeable and improves the retention rate of protein, the main body of the ultrafiltration membrane is made of PVDF material, characterized in that: The ultrafiltration membrane is also mixed with a repeating unit structure as shown below: ; The preparation method of the PVDF hollow fiber ultrafiltration membrane comprises the following steps: Step 1, mixing PVDF, a photoinitiator, a solvent, an additive, an initiator, and a hydrophilic monomer, and reacting them to obtain a casting solution; Step 2, preparing hollow fiber membrane fibers from the casting solution by a spinning method, and performing phase transformation in a coagulation solution to obtain a hollow fiber membrane; Step 3, subjecting the hollow fiber membrane to ultraviolet light irradiation treatment; In the step 1, the mass ratio of PVDF: photoinitiator: solvent: additive: initiator: hydrophilic monomer is 15-25: 0.1-1: 45-65: 5-18: 0.1-1: 1-10; The photoinitiator was 4-acryloxybenzophenone; The hydrophilic monomer is one of acrylamide, methyl acrylate, n-butyl acrylate, and butyl methacrylate; In the step 1, the reaction conditions are: reacting at 40-80° C. for 2-10 hours under inert gas conditions, and the inert gas is nitrogen or argon; In the step 3, the ultraviolet irradiation power is 250W and the irradiation time is 5-20min.

2. The use according to claim 1, characterized in that: The initiator is one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate; The solvent is any one of N,N-dimethylformamide, N,N-dimethylacetamide, acetone, tetrahydrofuran and glacial acetic acid; The additive is at least one of polyvinyl pyrrolidone-k30, polyvinyl pyrrolidone-k90, ethylene glycol, propylene glycol, glycerol, polyethylene glycol, LiCl, CaCl2, and polyvinyl alcohol.

3. The use according to claim 1, characterized in that: In the step 2, the conditions during the spinning process are: the casting liquid and the core liquid are extruded under a pressure of 0.1-0.5 MPa, and the extrusion flow rate is 7-20 m / min; In the step 2, the core liquid temperature is 15-75°C, and the core liquid composition is 20wt% N,N-dimethylformamide; the coagulation bath temperature is 15-75°C, and the composition is water.

4. The use according to claim 1, characterized in that: In the step 2, before the coagulation bath, the membrane filaments pass through an air bath of 1-30 cm.

Citation Information

Patent Citations

  • A pollution-resistant polyvinylidene fluoride hollow fiber membrane and its preparation method

    CN106334463B

  • Large-flux enhanced hollow fiber membrane and preparation method thereof

    CN110201559A

  • Preparation of hydrophilic polyvinylidene fluoride microporous membrane

    CN1704152A

  • Preparation method for hydrophilia polyvinylidene fluoride hollow fiber membrane

    CN104117294A

  • Ultraviolet cross-linking peripheral leakage preventing film material and preparation method thereof

    CN106893023A

Cited By

  • Polyvinylidene fluoride hollow fiber microfiltration membrane and preparation method thereof

    CN122183405A